Supporting Indigenous Students in Science and STEM Education: A Systematic Review - Qingna Jin (MDPI AG, 2021)
There are a growing number of education programs in science and STEM education with the aim of improving educational outcomes for Indigenous students who have long been underrepresented in current education systems. The aim of this study is to systematically review empirical research from 2011 to 2020 that reported programs to support Indigenous students in science and STEM education. A total of 24 studies were included in this review. These programs involved student participants from all K to 12 grade levels and occurred in both formal and informal contexts. Most of the programs employed multifaced approaches, and cultural relevance and scientific inquiry practice were the two main features of the programs. All the programs had reported positive outcomes in relation to Indigenous students' science learning, understanding of their own cultures and traditions, and/or the complementarity of Western science and Indigenous knowledge.